Motor Speed Control Sensor Using Hall Effect Sensor Based on IoT - Zumhari; Mardiana; Hasnita, Ulfa (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
A device will be designed as a DC motor rotation speed controller using a hall sensor based on Esp 32. Broadly speaking, this device consists of a DC motor, hall sensor, microcontroller and driver. The purpose of this design is to control the speed of the DC motor by pulse width regulation (PWM) method. The way this tool works is that the microcontroller is programmed to compare the motor rotation speed detected by the hall sensor to the input motor rotation speed and the display data will be displayed in real time via Android or PC. Thus the rotation speed of the DC motor can be controlled as expected. For this reason, this rotation speed control tool can be used for certain purposes, for example in the control process in the industrial world.